Optimization of Logistics Support on Natuna Island as a Base Carrier in Uploading the Sovereignty of the Republic of Indonesia - Suryawan, Anom (IJOSMAS, 2023)
Natuna Island has a strategic and important geographical position for the Unitary State of the Republic of Indonesia (NKRI), especially in maintaining maritime sovereignty in the North Natuna Sea. In facing complex challenges related to upholding sovereignty in the region, the Indonesian Navy needs reliable and efficient logistical support. Therefore, it is necessary to optimize the logistics support system which includes the procurement, storage, distribution and maintenance of the resources needed to carry out military operations on Natuna Island. This research will use qualitative and quantitative approaches by conducting field surveys, interviews with related parties, and analysis of relevant data. The research focus will include maintenance support on Natuna Island, existing supply support, base facility support, and optimal training and personnel support. The results of this study are expected to provide valuable recommendations for the Indonesian Navy in increasing the effectiveness and efficiency of logistical support on Natuna Island. By optimizing the logistics support system, it is hoped that military operations can be carried out more efficiently, strengthen the sovereignty of NKRI, and maintain security in the strategic area of the North Natuna Sea